Organosilicone elastomer capable of being self-repaired at room temperature, preparation method and metal coordination organosilicone elastomer

By introducing diarylethylene optical switch molecules and isocyanate into silicone rubber, a silicone elastomer network is constructed, which solves the problem of low self-healing efficiency at room temperature in the prior art, and achieves fast and efficient self-healing and excellent light response performance.

CN119490660AActive Publication Date: 2025-02-21BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202311028065.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

In the prior art, materials with self-healing properties have low self-healing efficiency at room temperature, which takes a long time to achieve a healing rate of 100%, and have weak light response characteristics, requiring the use of multiple light sources and a longer time to repair.

Method used

By using silicone rubber that is not easy to absorb water and diaryl ethylene with stronger light stability as raw materials, diaryl ethylene-type optical switching molecules containing aldehyde groups at both ends and difunctional isocyanate onto the main chain of the silicone rubber to form imine Bonds and urea groups to build a silicone elastomer network.

Benefits of technology

It achieves rapid self-healing at room temperature, achieves high-efficiency self-healing in just a short time, and only one light source is needed for repair, improving the light response and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490660A_ABST
    Figure CN119490660A_ABST
Patent Text Reader

Abstract

The invention discloses an organic silicon elastomer capable of being self-repaired at room temperature, a preparation method and a metal coordination organic silicon elastomer. The preparation method comprises the following steps: S1, dissolving silicone rubber and a diarylethene derivative in a first solvent, and reacting to obtain a first product; and S2, adding bifunctional isocyanate into the first product, and reacting to obtain the organic silicon elastomer capable of being self-repaired at room temperature. The organic silicon elastomer prepared by the invention has excellent light response performance and light healing performance, can realize self-healing at normal temperature, and can be repeatedly processed. On one hand, in the self-healing process, only one light source is used, and practical application is facilitated. On the other hand, self-healing can be achieved in a short time, and the self-healing efficiency is remarkably improved. In addition, the metal coordination organic silicon elastomer prepared by the invention also has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organosilicon polymers, and more particularly to an organosilicon elastomer capable of self-repairing at room temperature, a preparation method and a metal-coordinated organosilicon elastomer. Background Art

[0002] Polymers with self-healing properties have attracted much attention because they can enhance the durability, functionality and reliability of materials in practical applications. In recent years, many polymers with self-healing properties have been developed and reported. In particular, optically responsive self-healing. Using light as a stimulus, it can be applied locally to the damaged area and provides the possibility of healing under harsh conditions (such as water and sub-zero conditions). "A Self-repairing transparent film with reprocessable, ultra-high strength and outstanding elasticity based on interlocking hydrogenbonds and reversible topological networks" [Chemical Engineering Journal 456 (2023)] discloses a poly (thiourethane-urea) (PTUU) film with interlocking hydrogen bonds (IHB) and reversible topological networks. IHB gives the film high tensile strength (61.6MPa) and scratch resistance, but the self-healing performance of the PTUU film is reduced, and high temperature driving is required for self-healing to occur, which requires higher conditions than materials that can self-heal at room temperature.

[0003] "A photoresponsive azopyridine-based supramolecular elastomer for self-healing strain sensors" [Chemical Engineering Journal 395(2020))] discloses a metal supramolecular elastomer containing azopyridine, realizing the possibility of photohealing under mild conditions. Azo and its derivatives have excellent photoresponsive properties, which can convert light energy into mechanical response through trans-to-cis isomerization of the azo part when exposed to UV stimulation. Azopyridine not only has the common feature of azo to exhibit photoisomerization ability, but also the pyridine group can coordinate with transition metal ions and lanthanum ions in self-healing polymers, such as iron, zinc and europium, to achieve dynamic optical recovery based on metal-ligand systems. During the photorepair process, the cut surface was irradiated with 365nm and 450nm light sources, respectively, and the breaking and renewal of coordination bonds occurred simultaneously. In the repair test, the samples showed healing behavior after 90min (365nm) and 20min (450nm) of irradiation treatment, respectively. The healing rate was 100% after 24 hours of repair at room temperature, while only 46.1% efficiency could be achieved within 12 hours.

[0004] Although the metal supramolecular elastomer containing azopyridine can achieve light healing at room temperature, the stability of azo polymers is relatively weak, which has a certain impact on the metal supramolecular elastomer containing azopyridine. In addition, the healing process requires irradiation with two light sources, 365nm and 450nm, respectively, and the irradiation time is also long, which is inconvenient in practical applications. In addition, the self-healing efficiency in a short period of time is less than half, and it takes a day to heal, which is a long healing time. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a self-repairing organosilicon elastomer at room temperature. The present invention adopts silicone rubber that is not easy to absorb water and diarylethenes with stronger light stability as raw materials, introduces diarylethenes-type optical switch molecules containing aldehyde groups at both ends and difunctional isocyanates into the main chain of silicone rubber, generates imine bonds and urea groups, and forms an organosilicon elastomer network.

[0006] One of the purposes of the present invention is to provide a self-healing silicone elastomer at room temperature. The structure of the silicone elastomer is shown in the following formula (I):

[0007]

[0008] In formula (I), R1 is methyl or vinyl; R2 is C1-C3 alkyl; R3 is -(CH2)6, Any of the following;

[0009] n=12~18; m=10~20; j=10~20.

[0010] The second object of the present invention is to provide a method for preparing the silicone elastomer of the first object of the present invention.

[0011] The method comprises:

[0012] S1: dissolving silicone rubber and a diarylethene derivative in a first solvent, reacting to obtain a first product;

[0013] S2: adding difunctional isocyanate to the first product to react and obtain a silicone elastomer that is self-repairable at room temperature.

[0014] The following solutions can be adopted:

[0015] Silicone rubber and diarylethene derivatives are dissolved in a first solvent and reacted at room temperature. After a certain reaction time, thin layer chromatography is used to confirm whether the diarylethene derivatives are completely reacted. If the diarylethene derivatives are completely reacted, the reaction is considered to be complete and a first product is obtained. Then, difunctional isocyanate is added to the first product and reacted at room temperature. After the reaction is completed, the solvent is volatilized and dried to obtain a yellow silicone elastomer.

[0016] In a preferred embodiment of the present invention, the silicone rubber is aminopropyl-terminated polydimethylsiloxane or aminopropyl-terminated methylvinyl silicone rubber. The diarylethene derivative is any one of 4,4'-(perfluorocyclopent-1-ene-1,2-diyl)bis(5-methylthiophene-2-carboxaldehyde), 4,4'-(perfluorocyclopent-1-ene-1,2-diyl)bis(5-ethylthiophene-2-carboxaldehyde), and 4,4'-(perfluorocyclopent-1-ene-1,2-diyl)bis(5-propylthiophene-2-carboxaldehyde). The difunctional isocyanate is any one of isophorone diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, meta-xylene diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate. The first solvent is any one of dichloromethane, tetrahydrofuran, and chloroform. The technicians can select appropriate silicone rubber, diarylethene derivative, difunctional isocyanate and first solvent according to actual conditions.

[0017] In a more preferred embodiment of the present invention, the structure of the aminopropyl-terminated polydimethylsiloxane is shown in the following formula (II):

[0018]

[0019] In formula (II), n=16 to 18; or

[0020] The structure of the aminopropyl-terminated methyl vinyl silicone rubber is shown in the following formula (III):

[0021]

[0022] In formula (III), n=12-15.

[0023] The reaction equation for preparing silicone elastomer is as follows

[0024]

[0025] The organic silicone elastomer is an open-ring body, which forms a closed-ring body under ultraviolet light irradiation; the closed-ring body returns to the initial open-ring body under visible light irradiation. Its photoisomerization reaction is as follows

[0026]

[0027] In a preferred embodiment of the present invention, the molar ratio of the silicone rubber, the diarylethene derivative, and the difunctional isocyanate is 1:0.3-0.5:0.5-0.7. The technician can select a suitable molar ratio of the silicone rubber, the diarylethene derivative, and the difunctional isocyanate according to actual needs. Furthermore, in step S1, the reaction time is 4-6 hours; in step S2, the reaction time is 0.5-1 hour. The technician can select a suitable reaction time according to actual needs.

[0028] The third object of the present invention is to provide a metal-coordinated organosilicon elastomer that can self-repair at room temperature, wherein the metal-coordinated organosilicon elastomer is prepared by the following method:

[0029] The organometallic complex is dissolved in a second solvent, and the organosilicon elastomer described in one of the purposes of the present invention or the organosilicon elastomer obtained by the method of the second purpose of the present invention is added to react to obtain a metal-coordinated organosilicon elastomer that can self-repair at room temperature.

[0030] The following solutions can be adopted:

[0031] The organometallic complex is dissolved in a second solvent, and the organosilicon elastomer described in the first object of the present invention or the organosilicon elastomer obtained by the method of the second object of the present invention is added to react at room temperature. After the reaction is completed, the solvent is volatilized and dried to obtain a yellow metal-coordinated organosilicon elastomer.

[0032] In a preferred embodiment of the present invention, the organometallic complex is any one of tetrakis(acetonitrile)palladium tetrafluoroborate, zinc acetate, and zinc diethyldithiocarbamate. The second solvent is any one of acetonitrile, chloroform, and ethyl acetate. Technicians can select suitable organometallic complexes and second solvents according to actual needs. Furthermore, the amount of the organometallic complex is related to the silicone rubber used in the preparation of the organosilicon elastomer described in one of the purposes of the present invention. Specifically, the molar ratio of the silicone rubber to the organometallic complex is 1:0.08 to 0.24. Technicians can select suitable amounts of the organometallic complex according to actual needs.

[0033] Taking the organometallic complex as palladium tetra(acetonitrile)tetrafluoroborate and the silicone rubber as aminopropyl-terminated polydimethylsiloxane as an example, the metal coordination part formed by the room temperature self-healing organosilicon elastomer and the organometallic complex is as follows:

[0034]

[0035] In another preferred embodiment of the present invention, the reaction time is 0.5 to 1 h. Technicians can select a suitable reaction time according to actual needs.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The organosilicon elastomer prepared by the present invention has excellent light response performance and light healing performance, can achieve self-healing at room temperature, and can be processed repeatedly. On the one hand, only one light source is needed in the self-healing process, which is convenient for practical application. On the other hand, it can achieve self-healing in a short time, and the efficiency of self-healing is significantly improved. In addition, the metal-coordinated organosilicon elastomer prepared by the present invention also has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 ATR-IR spectra of PDMS-DTEM-IPDI prepared in Example 1 of the present invention and PDMS-DTEM-IPDI@Pd-16% prepared in Example 2;

[0039] Figure 2 This is the ultraviolet absorption spectrum of PDMS-DTEM-IPDI prepared in Example 1 of the present invention under 254nm ultraviolet light irradiation;

[0040] Figure 3 This is the ultraviolet absorption spectrum of PDMS-DTEM-IPDI prepared in Example 1 of the present invention under 580nm yellow light irradiation;

[0041] Figure 4This is the ultraviolet absorption spectrum of PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 of the present invention under 254nm ultraviolet light irradiation;

[0042] Figure 5 This is the ultraviolet absorption spectrum of PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 of the present invention under 580nm yellow light irradiation;

[0043] Figure 6 1 is a stress-strain curve diagram of two PDMS-DTEM-IPDIs in Example 1 of the present invention;

[0044] Figure 7 The stress-strain curves of four PDMS-DTEM-IPDI@Pd-16% of Example 2 of the present invention;

[0045] Figure 8 This is a micrograph of PDMS-DTEM-IPDI@Pd-16%- before ring-opening healing in Example 2 of the present invention;

[0046] Fig. 9 This is a micrograph of PDMS-DTEM-IPDI@Pd-16%-ring-opening healing in Example 2 of the present invention;

[0047] Fig.10 This is a micrograph of PDMS-DTEM-IPDI@Pd-16%- before closed-loop healing in Example 2 of the present invention;

[0048] Fig.11 This is a micrograph of the PDMS-DTEM-IPDI@Pd-16%-closed-loop healing of Example 2 of the present invention;

[0049] Fig.12 ATR-IR spectrum of PDMS-IPDI prepared in Comparative Example 1 of the present invention;

[0050] Fig.13 This is the ultraviolet absorption spectrum of PDMS-IPDI prepared in Comparative Example 1 of the present invention;

[0051] Fig.14 This is the ultraviolet absorption spectrum of PDMS-IPDI prepared in Comparative Example 1 of the present invention under 254nm ultraviolet light irradiation;

[0052] Fig.15 Schematic diagram of the PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 of the present invention being applied to information writing and erasing;

[0053] Fig.16Schematic diagram of the application of PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 of the present invention as a UV protection layer;

[0054] Fig.17 It is a schematic diagram of the micro-trace polytetrafluoroethylene mold surface;

[0055] Fig.18 Schematic diagram of the micro-trace polytetrafluoroethylene mold surface after spraying PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0056] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0057] In the present invention, PDMS is aminopropyl-terminated polydimethylsiloxane; DTEM is 4,4'-(perfluorocyclopent-1-ene-1,2-diyl)bis(5-methylthiophene-2-carboxaldehyde); and IPDI is isophorone diisocyanate.

[0058] Example 1

[0059] Weigh 4 g of PDMS and 0.234 g of DTEM, dissolve PDMS and DTEM in dichloromethane, stir at room temperature for 4 hours, confirm by thin layer chromatography that DTEM has reacted completely, then weigh 0.117 g of difunctional isocyanate IPDI, add it to the system, and continue stirring at room temperature for 1 hour to obtain PDMS-DTEM-IPDI.

[0060] The PDMS-DTEM-IPDI prepared in Example 1 was subjected to ATR-IR measurement, and the results were as follows: Figure 1 Before the test, the reaction raw material polydimethylsiloxane (PDMS) was characterized by ATR-IR, and it was found that 1000~1100cm -1 The characteristic peak of Si-O-Si appeared nearby, 2963cm -1 Nearby is the vibration absorption peak of the silicon methyl group on PDMS, 1600cm -1 The NH bending vibration peak of -NH2 appeared near the reaction; the reaction raw material dithienylethylene containing dialdehyde group was characterized by DTEM, and it was found that 1672cm -1 The stretching vibration peak of C=O is near 2849cm, which corresponds to the stretching vibration peak of C=O of aldehyde group in DTEM molecule. -1The stretching vibration of the aldehyde protons appears nearby, which is the Fermi resonance peak of the aldehyde group and the characteristic peak of the aldehyde group.

[0061] Figure 1 The ATR-IR spectrum of PDMS-DTEM-IPDI is shown. Figure 1 It can be seen that 2849cm -1 The Fermi resonance peaks of the aldehyde groups nearby and 1600 cm- -1 The characteristic peak of the amino group nearby disappeared, and at the same time, the peak of PDMS-DTEM-IPDI at 1634 cm -1 A new peak appeared near the PDMS system, which corresponds to the characteristic peak of the imine bond (-N=CH-), indicating that a Schiff base reaction occurred during the polymerization process, the aldehyde group on the DTEM molecule was consumed and a new imine bond was formed, and the imine bond was successfully introduced into the PDMS system. -1 There is a weak absorption peak near 1571 cm -1 The new peak nearby corresponds to the amide ⅠⅠ band in the urea group (i.e., the bending vibration of NH), 1298 cm -1 The new peaks appearing near the urea group correspond to the amide III band (i.e., the stretching vibration of CN), while the isocyanate -NCO peak at 2200 cm -1 The stretching band nearby did not appear, confirming that the added IPDI also fully participated in the reaction to form urea groups. The above results confirm that PDMS-DTEM-IPDI was successfully synthesized, and its structure is shown below

[0062]

[0063] Example 2

[0064] Weigh 4g PDMS and 0.234g DTEM, dissolve PDMS and DTEM in dichloromethane, stir at room temperature for 4h, confirm that DTEM is completely reacted by thin layer chromatography, then weigh 0.117g difunctional isocyanate IPDI, add it to the system, and continue stirring at room temperature for 1h to obtain PDMS-DTEM-IPDI. Weigh 0.22g Pd(CH3CN)4(BF4)2, ultrasonically dissolve it in 5ml acetonitrile to obtain Pd salt solution. Add 1705μL of Pd salt solution to PDMS-DTEM-IPDI, the molar ratio of Pd(CH3CN)4(BF4)2 to PDMS is 16%, and continue stirring at room temperature for 0.5h. After evaporating and drying the solvent, the yellow elastomer PDMS-DTEM-IPDI@Pd-16% is obtained.

[0065] The PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 was subjected to ATR-IR measurement, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that PDMS-DTEM-IPDI at 1634 cm -1 The characteristic peak of the imine bond near 1670 cm -1 A new peak appeared near the imine bond, which was attributed to the coordination bond formed after the imine bond coordinated with Pd, causing the characteristic peak of the imine bond to blue shift, confirming the coordination effect of Pd and the imine bond; at the same time, the urea group in PDMS-DTEM-IPDI also participated in the coordination, and the amide I band, amide II band and amide III band all moved significantly before and after the coordination. After the coordination, the amide I band shifted from 1724cm -1 Nearby blue shift to 1728cm -1 Nearby, the amide II band starts at 1571 cm -1 Nearby redshift to 1547cm -1 Nearby, the amide III band from 1298cm -1 Nearby blue shift to 1330cm -1 , confirming that there is coordination between Pd and both N and O atoms on the urea group. The above results confirm that effective coordination bonds can be formed between PDMS-DTEM-IPDI and metal Pd salts.

[0066] The UV-visible absorption spectrum of the PDMS-DTEM-IPDI prepared in Example 1 was measured. The test method was: PDMS-DTEM-IPDI was spin-coated on a glass sheet and then tested for UV absorption spectrum. The results were as follows: Figure 2 and Figure 3 shown. Figure 2 In the experiment, the elastomer PDMS-DTEM-IPDI produced two new peaks in the visible light region, located at 348-421nm and 446-717nm respectively. At the same time, the absorption peak at 266nm in the ultraviolet light region decreased significantly, and two isosbestic points appeared, located at 238nm and 309nm respectively. After 30 minutes of illumination, the elastomer basically reached a photostable state. Figure 3 In the experiment, the two new peaks of the elastomer PDMS-DTEM-IPDI in the visible light region decreased significantly until they disappeared, and at the same time, the absorption peak at 266nm in the ultraviolet region recovered again, and two isosbestic points appeared, located at 241nm and 308nm, respectively. After 4 minutes of illumination, the elastomer basically reached a photostable state. It was confirmed that the PDMS-DTEM-IPDI prepared in Example 1 had obvious photoreversibility.

[0067] The same method was used to measure the UV-visible absorption spectrum of PDMS-DTEM-IPDI@Pd-16% prepared in Example 2. The results were as follows: Figure 4 and Figure 5 shown. Figure 4In the experiment, the elastomer PDMS-DTEM-IPDI@Pd-16% produced two new peaks in the visible light region, located at 354-446nm and 455-748nm respectively. At the same time, the absorption peak at 265nm in the ultraviolet light region decreased significantly, and two isosbestic points appeared, located at 240nm and 310nm respectively. After 30 minutes of illumination, the elastomer basically reached a photostable state. Figure 5 In the elastomer PDMS-DTEM-IPDI@Pd-16%, the two new peaks in the visible light region decreased significantly until they disappeared, and at the same time, the absorption peak at 266nm in the ultraviolet region recovered again, and two isosbestic points appeared, located at 240nm and 308nm, respectively. After 4 minutes of illumination, the elastomer basically reached a photostable state. It is confirmed that the PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 has obvious photoreversibility.

[0068] The self-healing performance of PDMS-DTEM-IPDI prepared in Example 1 was tested. The fracture toughness W was used to characterize the mechanical properties of the elastomer. W was defined as the energy dissipated during the fracture process and was calculated by integrating the area under the stress-strain curve:

[0069]

[0070] In formula (1), ε is strain and σ is stress.

[0071] The ratio of the sample's healed fracture toughness to the sample's original fracture toughness is defined as the self-healing efficiency η

[0072]

[0073] In formula (2), W1 is the energy dissipated in the fracture process before healing, and W2 is the energy dissipated in the fracture process after healing.

[0074] The method for testing the self-healing performance is as follows: use a national standard type 3 dumbbell cutter to punch and cut the block elastomer to obtain a dumbbell-shaped spline (length 50mm, narrow parallel width 4mm). Use a Mark 10 tensile testing machine to test the stress-strain curve of the PDMS-DTEM-IPDI elastomer at room temperature at a tensile rate of 50mm / min. At least five samples were tested for each sample to obtain the stress-strain curve of the PDMS-DTEM-IPDI before self-healing. The above dumbbell-shaped spline was completely cut with a blade, and the two ends of the section were in contact with each other, and kept in an oven at 25°C for 12 hours without any external stimulation. It should be noted that the oven is an enclosed space, a dark space without light. After 12 hours in the oven, the stress-strain curve of the elastomer was tested at room temperature using Mark 10 at a tensile rate of 50mm / min to obtain the stress-strain curve of the PDMS-DTEM-IPDI after self-healing. The results are as follows Figure 6As shown. Figure 6 It can be seen that the stress-strain curves before and after self-healing have almost no significant changes. The tensile strength and elongation at break before and after self-healing are within a reasonable error and the values ​​are similar, and the fracture toughness is 0.0034. It can be seen that there is no significant change in the mechanical properties before and after self-healing. According to formula (1) and formula (2), the self-healing efficiency of PDMS-DTEM-IPDI is 100%.

[0075] The self-healing performance of PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 was tested in the same manner as above. The results are as follows: Figures 7 to 11 shown. Figure 7 The stress-strain curves of four PDMS-DTEM-IPDI@Pd-16% are shown. The fracture toughness and self-healing efficiency of PDMS-DTEM-IPDI-@Pd-16%-Open (open ring state) and PDMS-DTEM-IPDI-@Pd-16%-Close (closed ring state) are calculated according to equations (1) and (2) (as shown in Table 1).

[0076] Table 1 Fracture toughness and self-healing efficiency of PDMS-DTEM-IPDI-@Pd-16%-Open (open ring state) and PDMS-DTEM-IPDI-@Pd-16%-Close (closed ring state)

[0077]

[0078] according to Figure 7 It can be seen that PDMS-DTEM-IPDI@Pd-16%-Open (open loop state) can be stretched to 800% at a speed of 50 mm / min. After self-healing at room temperature for 12 hours, it can be stretched to 610%, and the healing efficiency is 62.5%. Similarly, PDMS-DTEM-IPDI@Pd-16%-Close (closed loop state) can be stretched to 870% at a speed of 50 mm / min. After self-healing at room temperature for 12 hours, it can be stretched to 870%, and the healing efficiency is 88.5%.

[0079] The self-healing efficiency of PDMS-DTEM-IPDI-@Pd-16%-Open (open ring state) is 62.5%, and the self-healing efficiency of PDMS-DTEM-IPDI@Pd-16%-Close (closed ring state) is 88.5%. This confirms that the introduction of DTEM molecules into the PDMS-DTEM-IPDI-@Pd-16% elastomer can achieve the controllability of the self-healing properties of the elastomer. This can be attributed to the fact that when the DTEM is closed, the planarity of the molecular configuration increases, which changes the distance between the imine bonds connected to the DTEM, which is more conducive to the dynamic repair between different imine bonds, thereby improving the self-healing properties of the material. In addition, Figure 7 It is shown that the mechanical properties can be tuned by DTEM open-closed loop.

[0080] Figure 8 and Fig. 9 Micrographs of PDMS-DTEM-IPDI@Pd-16%-Open before and after healing are shown. Figure 8 and Fig. 9 It can be seen that after 12 hours of autonomous healing, the incision of the open-loop elastomer was not completely healed. Fig.10 and Fig.11 Micrographs of PDMS-DTEM-IPDI@Pd-16%-Close before and after healing are shown. Fig.10 and Fig.11 It can be seen that after 12 hours of exposure to natural light or avoiding light, the incision almost disappears, confirming that the PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 has the performance of self-healing at room temperature and can achieve self-healing in a short time. The efficiency of self-healing is significantly improved, and it can be used for coating scratch repair.

[0081] By comparison, it can be found that the fracture toughness of PDMS-DTEM-IPDI is 0.0034, and the fracture toughness of PDMS-DTEM-IPDI-@Pd-16% is 0.6151, which means that the introduction of metal coordination bonds further enhances the mechanical properties of silicone elastomers.

[0082] Comparative Example 1

[0083] Weigh 4 g of PDMS, dissolve it in dichloromethane, weigh 0.117 g of difunctional isocyanate IPDI, add it to the system, and continue stirring at room temperature for 1 hour to obtain PDMS-IPDI. ATR-IR measurement was performed on the PDMS-IPDI prepared in Comparative Example 1. The results are as follows: Fig.12 As shown. Fig.12 It can be seen that 3335cm -1 is the absorption peak of -NH in urea group, 2962cm -1is the stretching vibration peak of methyl -CH, 1740~1600cm -1 It is the carbonyl absorption region in the urea group, 1100~1000cm -1 The double peak at 2200 cm-1 is the bending vibration peak of the polysiloxane skeleton Si-O-Si. -1 The nearby stretching band did not appear, confirming that the added IPDI participated in the reaction to form urea groups.

[0084] The UV-visible absorption spectrum of PDMS-IPDI prepared in Comparative Example 1 was measured, and the results were as follows: Fig.13 and Fig.14 As shown. Fig.13 It can be seen that its maximum absorption wavelength is 202nm, which is significantly different from the ultraviolet absorption spectrum of PDMS-DTEM-IPDI prepared in Example 1. Fig.14 It can be seen that after irradiation with ultraviolet 254nm light for 10min, the maximum absorption wavelength is still 202nm, which is consistent with Fig.13 There is no change compared to the original material, and no new peak appears in the visible light band, proving that there is no photochromic phenomenon.

[0085] Comparative Example 2

[0086] 4 g PDMS and 0.234 g DTEM were weighed, PDMS and DTEM were dissolved in dichloromethane, and stirred at room temperature for 4 hours. However, no elastomer was formed.

[0087] Application Example 1

[0088] The PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 is used for writing and erasing information. The specific operation is as follows: the PDMS-DTEM-IPDI@Pd-16% elastomer prepared in Example 2 is placed on the surface of a vessel, which has a yellow background [such as Fig.15 (a)]. When exposed to ultraviolet light for 1 min, the surface of the elastomer changes from yellow to blue [as shown in Fig.15 (b)]. Place the transparent bottom mask QR code on the surface of the elastomer [as shown Fig.15 (c)], then irradiate with yellow light for 3 min, remove the QR code mask, and the QR code information can be displayed on the surface of the elastomer [as shown in Fig.15 (d)]. The yellow light was used to irradiate the surface of the elastomer containing the QR code information for 3 min, and the blue color completely faded and returned to yellow [as shown in Fig.15 This application example also reflects the photochromic properties of the silicone elastomer of the present invention.

[0089] Application Example 2

[0090] The PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 was applied to a reusable anti-ultraviolet protective layer. The specific operation was as follows: the PDMS-DTEM-IPDI@Pd-16% elastomer prepared in Example 2 was dissolved in an ethanol solvent, the concentration of the elastomer solution was 0.4 g / ml, and it was placed on the surface of a glass sheet by spin coating [such as Fig.16 (a)]. Under the irradiation of ultraviolet light (365nm), its surface quickly turns blue and blocks the ultraviolet rays from continuously irradiating the internal matrix [as shown in Fig.16 (b)]. It can be restored under yellow light (580nm) [as shown Fig.16 (c)]. The above process can be repeated.

[0091] Application Example 3

[0092] The PDMS-DTEM-IPDI@Pd-16% prepared in Example 2 was used as a micro-trace developer. The specific operation was as follows: the prepared PDMS-DTEM-IPDI@Pd-16% elastomer was dissolved in an ethanol solvent to prepare an elastomer solution with a concentration of 0.02 g / ml, and the elastomer solution was sprayed on the surface of a polytetrafluoroethylene mold with scratches (such as Fig.17 After the solvent evaporates completely, use 254nm ultraviolet light to illuminate the surface, and the scratch marks will be clearly visible (as shown in the figure). Fig.18 shown).

Claims

1. A self-repairable silicone elastomer at room temperature, characterized in that: The structure of the silicone elastomer is shown in the following formula (I): In formula (I), R1 is methyl or vinyl; R2 is C1-C3 alkyl; R3 is -(CH2)6, Any of the following; n=12~18; m=10~20; j=10~20.

2. A method for preparing an organic silicone elastomer as claimed in claim 1, characterized in that The method comprises: S1: dissolving silicone rubber and a diarylethene derivative in a first solvent, reacting to obtain a first product; S2: adding difunctional isocyanate to the first product to react and obtain a silicone elastomer that is self-repairable at room temperature.

3. The method according to claim 2, characterized in that: The silicone rubber is aminopropyl-terminated polydimethylsiloxane or aminopropyl-terminated methylvinyl silicone rubber; and / or The diarylethene derivative is any one of 4,4'-(perfluorocyclopent-1-ene-1,2-diyl)bis(5-methylthiophene-2-carboxaldehyde), 4,4'-(perfluorocyclopent-1-ene-1,2-diyl)bis(5-ethylthiophene-2-carboxaldehyde), and 4,4'-(perfluorocyclopent-1-ene-1,2-diyl)bis(5-propylthiophene-2-carboxaldehyde); and / or The difunctional isocyanate is any one of isophorone diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, meta-xylylene diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate; and / or The first solvent is any one of dichloromethane, tetrahydrofuran and chloroform.

4. The method according to claim 3, characterized in that: The structure of the aminopropyl-terminated polydimethylsiloxane is shown in the following formula (II): In formula (II), n=16 to 18; or The structure of the aminopropyl-terminated methyl vinyl silicone rubber is shown in the following formula (III): In formula (III), n=12-15.

5. The method according to claim 2, characterized in that: The molar ratio of the silicone rubber, the diarylethene derivative and the difunctional isocyanate is 1:0.3-0.5:0.5-0.

7.

6. The method according to claim 2, characterized in that: In step S1, the reaction time is 4 to 6 hours; and / or In step S2, the reaction time is 0.5 to 1 h.

7. A metal-coordinated silicone elastomer capable of self-repair at room temperature, characterized in that: The metal coordinated silicone elastomer is prepared by the following method: The organometallic complex is dissolved in a second solvent, and the organosilicon elastomer as claimed in claim 1 or the organosilicon elastomer obtained by the method of any one of claims 2 to 6 is added thereto for reaction to obtain a metal-coordinated organosilicon elastomer that is self-repairable at room temperature.

8. The metal-coordinated silicone elastomer according to claim 7, characterized in that: The organic metal complex is any one of tetrakis(acetonitrile)palladium tetrafluoroborate, zinc acetate, and zinc diethyldithiocarbamate.

9. The metal-coordinated silicone elastomer according to claim 7, characterized in that: The second solvent is any one of acetonitrile, chloroform and ethyl acetate.

10. The metal-coordinated silicone elastomer according to claim 7, characterized in that: The reaction time is 0.5 to 1 hour.

Citation Information

Patent Citations

  • Preparation method for dual-reversible-key self-healing silicone rubber capacitive pressure sensor at room temperature

    CN109764980A

  • Preparation method of organic gel with photochromism and fluorescence

    CN114058361A

  • Rare earth coordination type self-repairing organic silicon elastomer and preparation method thereof

    CN114805793A

  • Organosilicone elastomer, preparation method thereof, flexible sensor and preparation method thereof

    CN116082644A

  • Preparation method of organosilicon self-healing marine antifouling coating

    CN116254043A

Cited By

  • Self-repairing flexible electronic material based on non-covalent bond network and preparation method and application thereof

    CN121406139A